AN ANALYSIS OF STUDENTS’ ATTITUDE IN LEARNING ENGLISH AT ELEVENTH GRADE OF SMA NEGERI 2 GU - Fitria Fitria; Baharudin Baharudin; Asti Wahyuni B (English Education Journal, 2022)
The problem in this study was how were the students’ attitude in learning English at eleventh grade of SMA Negeri 2 Gu? This study aimed at determining and identifying students’ attitude in learning English in the eleventh grade of SMA Negeri 2 Gu. The design of this study was a descriptive qualitative. Subjects of the research were fifteen students of eleventh grade at SMA Negeri 2 Gu. Techniquies of data collection in this study were questionnaire and interviw. Techniques of data analysis used were data reduction, data display and conclusion. The result showed thwt te students had positive attitude in learning English, which consisted of aspect of cognitive attitude, aspect of affective attitude and aspect of behavior attitude. In all aspects students’ attitude were in the good category. Based on three aspects of attitudes, the most dominant aspect of attitude was the affective attitude aspect.